Industrial high pressure ethylene polymerization initiated by peroxide mixtures: A reduced mathematical model for parameter adjustment - Asteasuain, Mariano (2001)
We present a method for the adjustment of parameters in the mathematical modeling of industrial tubular reactors for high pressure polymerization of ethylene. We propose a reduced mathematical model for these reactors that aids in the task of model parameter update commonly done periodically in industrial plants. This reduced model was built from a detailed model for multiple peroxide and oxygen initiator systems we had developed before. Some of the assumptions in that rigorous model were reviewed in order to minimize computational effort. Good and faster predictions were obtained by assuming different constant jacket temperatures and pressures at each zone. Pressure pulse equations had to be included in the model. A simplification of the adjustment procedure is also proposed here. It consists in using only the reactions considered crucial for the description of this polymerization. The peroxide initiator and solvent mixtures were treated as fictitious unique initiator and solvent respectively. A procedure was established for the quick estimation of the kinetic parameters that represent initiator and solvent mixtures of different compositions. This resulted in a model that can be adjusted rapidly to predict the behavior of a specific industrial reactor. The reduced model was validated using experimental runs initiated by oxygen either alone or together with peroxide mixtures.